Ultrasonic vest for blind person / Nur Amalin Aisyah Abdul Hadi, Nuran Nadhirah Noor Azmi and Nurul Ain Manap - Abdul Hadi, Nur Amalin Aisyah; Noor Azmi, Nuran Nadhirah; Manap, Nurul Ain (2015)
Based on a study that been conducted on people with disabilities, found one problem which is the person that cannot be viewed or in a simple word person who are blind. Blindness is a condition of lacking visual perception and it is always described as severe visual impairment with residual vision. This situation has resulted in many difficulties to them in their normal work, lives, activities, and so on. Based on the investigation about daily activity characteristics and modes of the blind, the study found that the main difficulties are walking on the road, finding way, taking a bus and looking for usual life-arena. So if the blind people have a problem with this, the blind people feel awkward to perform in daily activities even to move in their own place with a lot of obstacles. Nowadays the city is booming and rapidly so the blind people felt themselves is one of the obstacles because of their disabilities. There are many aids for the blind person such as stick where this people should hold and always focus on the environment. This project has been created a special tool for the blind people in order to easier the movement to replace the stick. Apart from that, this project can help the blind to signal if there is an object or person of then or block their path. Therefore the blind people do not need to bother to make sure there are no obstacles in their path. With the project, the ultrasonic sensor will help blind people by signaling if there is an object in front of this type of person. The buzzer will work as if the ultrasonic sensor received the signal. The LED also will be set at the vest and is especially designed to give signal to other people at night. For a wider view, this project has yet to be used again in Malaysia. Thus, by applying this project, country’s name can be raised in the worldwide.